Velocity slip impact on the squeezing flow of water–CNTs and kerosene–CNTs nanofluids over a Riga surface - Subhajit Panda; Laila A. AL-Essa; Rupa Baithalu; S.R. Mishra; Anwar Saeed (Journal of Taibah University for Science, 2024)
In various industrial vis-a-vis technological applications, the study of squeezing flow of carbon nanotube (CNT) nanofluid past along the Riga surface is vital. The present article aims in examining the role of velocity slip in two distinct cases considering the flow of CNT–water and CNT–kerosene nanofluid over a Riga-squeezing surface. The Riga surface generates Lorentz force and provides a platform for enhancing heat transfer characteristics. Additionally, the inclusion of dissipative heat along with radiant heat and irregular heat supplier energies the heat transport phenomenon. The mathematical model endorsed with dimensional features is transmuted into nondimensional form by the implementation of similarity rules, and the results of several flow profiles are manipulated by employing the traditional “Runge–Kutta fourth-order” along with shooting scheme. The parametric analysis is presented through graphs, and the validation with earlier investigation is depicted via tabular form representing the numerical results in the particular case.